Analisis Pengaruh Influencer Marketing terhadap Keputusan Pembelian Generasi Z di Platform TikTok - Jopinus Saragih; Margono; Reno Triwan Padang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the effect of influencer marketing on Generation Z purchase decisions on TikTok and to develop an explanatory understanding of the underlying influence mechanisms. The research is motivated by the changing marketing landscape driven by digital technology and the growing role of social media in consumer behavior. TikTok is strategically important due to its algorithmic distribution that amplifies content reach, while Generation Z’s characteristics—digital-native, visual-oriented, and short attention span—make them a distinctive target audience. The research employs a mixed-methods sequential explanatory design, consisting of a quantitative phase using an online survey of 400 Gen Z respondents in Indonesia, followed by a qualitative phase involving in-depth interviews and netnography (30 informants and 50 TikTok accounts). The findings indicate that influencer marketing significantly affects Gen Z purchase decisions on TikTok. Influencer credibility is a critical factor influencing attitudes toward the product (β = 0.42, p < 0.001), while authenticity in content plays a stronger role in building trust in the influencer (β = 0.38, p < 0.001). Additionally, entertainment value increases engagement (β = 0.45, p < 0.001), and social proof enhances purchase intention (β = 0.32, p < 0.001). The influence operates through cognitive, affective, and social processes, further strengthened by TikTok’s algorithm that supports virality and accelerates social proof formation. The study concludes that Gen Z purchase decision-making is non-linear and multi-platform. It also proposes the TikTok Influencer Impact Model (TIIM) as an integrative framework linking input factors, processing mechanisms, and outcome stages. The results offer practical implications for brands, influencers, and TikTok in designing ethical and Gen Z-relevant marketing strategies.